(untitled) (Journal of Engineering Studies and Research, 2022)
In order to achieve the aim of adjusting heights and angles of lamps in sledge tests, detailed requirements were analyzed, and the implementation scheme was devised. The prototype of the elevating device was designed to validate the effect. Both the power circuit and the control circuit were researched on to power and control the 4 3-phase asynchronous motors respectively. An effective solution was provided to the adjustment of the essential parameters in sledge tests’ illumination. Manual control and remote control modes were both designed and employed to make the necessary adjustments possible. On-site application validated that the elevating device was effective and could be used to adjust parameters relevant with lamps’ spatial positions.